2005
DOI: 10.1111/j.0038-4941.2005.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Reform and Teenage Girls*

Abstract: Objectives. Although the problems of teenage girls figured prominently in the passage of welfare reform legislation in 1996, there has been relatively little research on the effects of the new law on this population. This article attempts to fill this gap. Methods. The article employs a difference‐in‐difference methodology to assess program impacts, making use of data from the March Current Population Survey for the years 1989–2001. Results. The main findings are that the 1996 legislation increased school a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…In addition, welfare rules do not allow minor mothers to receive welfare if they move away from their family home and are not in school. As indicated earlier, welfare reform reduced high school dropout, and the effects were stronger for girls than for boys (Dave, Corman & Reichman 2012;Koball 2007;Offner 2005). Since having a criminal background is a deterrent to getting a job in the legal sector, and since schooling can be a substitute for illegal behavior, it is plausible that welfare reform would lead to decreases in crime, particularly among girls.…”
Section: Parental Modelingmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, welfare rules do not allow minor mothers to receive welfare if they move away from their family home and are not in school. As indicated earlier, welfare reform reduced high school dropout, and the effects were stronger for girls than for boys (Dave, Corman & Reichman 2012;Koball 2007;Offner 2005). Since having a criminal background is a deterrent to getting a job in the legal sector, and since schooling can be a substitute for illegal behavior, it is plausible that welfare reform would lead to decreases in crime, particularly among girls.…”
Section: Parental Modelingmentioning
confidence: 82%
“…That is, the new regime was expected to mainstream not only poor mothers, but also their children. Studies have found that 4 welfare reform reduced high school dropout and teen fertility (Dave, Corman & Reichman 2012, Kaestner, Korenman & O'Neill 2003Koball 2007;Lopoo & Deleire 2006;Miller & Zhang 2012;Offner 2005), providing some support for this argument. However, few studies have considered how the new regime has affected teens more broadly.…”
mentioning
confidence: 99%
“…The estimated effects, however, tend to be modest. For example, Offner (2005) finds that TANF is responsible for a 1.1 to 1.6 percentage point decrease in teen birth rates. In our analysis, we include indicators for whether a state-year observation has in place a welfare waiver policy or if it had implemented TANF.…”
Section: Policies Consideredmentioning
confidence: 99%
“…Here we examine the effects of welfare reform on school enrollment, using data from the CPS's October supplement files from 1990 to 2005 (U.S. Bureau of Labor Statistics 1990-2005. This provides a useful comparison with other observational studies in the welfare reform literature that use survey data (for example , Offner 2005;Dave, Reichman, and Corman 2009).…”
Section: Results For Self-reported School Enrollment Ratesmentioning
confidence: 99%
“…The lack of positive effects noted by Hao and Cherlin may be the result of their limited sample sizes and the short-term nature of their estimates, which were computed immediately after welfare reforms. 4 Offner (2005) and Dave, Reichman, and Corman (2009) provide the studies closest to our analysis of survey data from the October CPS (U.S. Bureau of Labor Statistics 1990-2005 presented in Section 5. Both focus on teenage girls.…”
Section: Introductionmentioning
confidence: 99%